Inclusion in Rabbinic and Protestant Translations of the book of Proverbs (1865) History of Translations and Cultural Inclusion Terms of Reference (Damascus University Journal of arts and humanities sciences, 2021)
The Old Testament has been translated into many languages, including Arabic. There has been consecutive translation of it since Islamic antiquity. The Rabbinic translation, which rendered the Hebrew text into Arabic without a linguistic medium appeared later. It was followed by several Orthodox and Jesuit trials, including the Protestant translation. Those two translations were chosen to study the book of Proverbs, which is classified as one of the books of Wisdom; something that distances it from being either symbolical or historical, and makes the translation the subject of the translator's ideology starting from the incorporated cultural element be it Jewish, Aramaic or Islamist (Mu'tazila) of the first translation, or through the choice of the equivalent signs of origin, and the neutralization of the Rabbinic, Arabic, and Greek element of the second translation. The various Protestant translation of different authors has contributed to the multiplicity of the term of reference, mostly Christian, in contrast with the single reference of one author which carries multiple conflicting cultural facades when it comes to the Rabbinic translation. This has led to a change in the origin through the inclusion of those various verbal or interpretative elements in the book of Proverbs, which will be examined in the verses through a comparative study with the original Hebrew text or the culture terms or reference.